Integrasi Kegiatan Masyarakat Budaya Lokal dan Lembaga dalam Pendidikan Toleransi - Jazuli Mukhtar; Yunus Yunus; Ichwan Nugroho (Institut Agama Islam Negeri Kendari, 2021)
The research explains the form of local wisdom of Bugis culture as a cultural value that characterizes the Palopo people. The local wisdom developed in Palopo City is in line with the pluralistic Palopo culture developing in Indonesia. Palopo people has local wisdom values such as humanizing. These values are always preserved so that they become the glue of religious harmony in Palopo City. The type of this research is ethnography. The research findings show that knowledge and understanding of the cultural traditions of society that contain pluralism allow students to suspend suspicion or even wholly disappear negative things that students have understood about other religions. The concept of pluralism is seen from implementing the cultural philosophy in Palopo, namely Sipakatau, Sipakalebbi, and Sipakaingge. Two universities, IAIN Palopo and Andi Djemma University practice the local wisdom values. The results shows that personally, students who were actively involved in the implementation of local wisdom education felt that they had experienced significant changes. In the aspect of faith, they are increasingly convinced of their religion while still providing adequate space for a good and correct assessment of the truth of the teachings of other religious and cultural beliefs.